Perbandingan Hasil Belajar Matematika Peserta Didik SMP Selama Pembelajaran Daring dan Pembelajaran Tatap Muka - Ramadina, Luthfianisa; Lubab, Ahmad; Nugrahenny, Jo Estu (JRPM (Jurnal Review Pembelajaran Matematika), 2022)
This research was conducted to find out whether there is a significant comparison to the mathematical learning outcomes of students of class VIII SMPN 3 Waru when doing face-to-face learning and online learning. The learning results used in this study are the PAS scores of class VIII learners in odd and even semesters of the 2019/2020 school year. The method used in this study was ex post facto correlation and used the Wilcoxon test with the help of the SPSS 25 software. Wilcoxon's statistical test results showed the 2-tailed Asymptotic Significance was worth 0,506. Because 0,506>0,05 then H_a rejected and H_0 accepted, it can be concluded that this study shows no significant difference in the mathematical learning outcomes of SMPN 3 Waru learners when doing face-to-face and online learning.